Heritage protection in low-density areas: CIM Douro - Carlos Araújo; Paulo Barrosa; Tiago Gomes; Xavier Dias; Milena Carvalho; Susana Fonseca; Ana Guia; Susana Martins; Ana Branca Carvalho (Millenium)
Introduction: This study investigates safeguarding strategies for heritage in low-density territories within within the Intermunicipal Community of Douro (CIM Douro), exploring the challenges associated with the preservation of both cultural and natural heritage.